Density functional theory investigation of emerging two-dimensional heterostructured materials - Kistanov, Andrey (2019)
Over the last few years, many studies have been performed on two-dimensional (2D) materials, such as graphene, silicone and MoS2, owing to their unique properties and successful applications in nanoelectronics, photonics and other fields. It has been shown that the structural stability and various properties of 2D materials can be influenced by different factors, such as defect and strain engineering, electric field, edge functionalization, and adatom adsorption. Furthermore, the internal vacancy defects can easily emerge at the surface of 2D materials in the manufacturing process. Meanwhile, it is well known that 2D materials possess high chemical activity. Therefore, during the manufacturing and application of 2D materials, it is important to control their structural stability and properties which may change significantly under the influence of environmental and exploitation conditions. Hybrid 2D materials such as graphene-boron nitride (BN), graphene-silicene and graphene-MoS2 have also been found to be superior to their individual 2D counterparts in terms of structural stability and properties. For instance, chemically unstable 2D materials, like silicene and phosphorene, can be protected by their passivation by chemically more stable 2D materials, such as graphene and BN. The recent successful fabrication of several new 2D materials (phosphorene, borophene, InSe and antimonene) - has triggered increasing attention to these materials due to their distinctive opto-electronic and mechanical properties, such as a wide and tunable band gap, high carrier mobility and flexibility. However, these unique 2D materials are still poorly investigated. Therefore, this Ph.D. study has aimed to systematically investigate the atomic structure, opto-electronic properties and chemical activity of phosphorene, InSe, borophene and antimonene under the influence of various factors, such as large deformations, vacancies and molecules of the surrounding environment. In addition, heterostructures of these 2D materials have been considered. The investigations have been carried out within the framework of the density functional theory using first-principles calculations. The studies of the atomic structure, electronic properties and chemical activity of phosphorene under the strain and defect engineering have shown that phosphorene enables the withstanding of a large compressive strain and exhibits anisotropic electronic properties. Moreover, compressive strain and the presence of mono- (MV) and di- (DV) vacancy defects significantly alter the chemical activity of phosphorene as evidenced by the enhanced adsorption and charge transfer between the environmental molecules, such as H2O, O2 and NO, and phosphorene surface. Typical methods, such as defect engineering and surface functionalization, have been applied for the exploration of possible avenues for opening the band gap of borophene. The metallicity in borophene has been found to be immune to the surface functionalization and the presence of vacancies. More importantly, the anisotropy of the electronic properties and the nature of the orbitals at the Fermi level can be altered upon the surface functionalization, enabling the modulation of the borophene properties. Due to the high density of itinerant electrons in the atomically thin borophene sheet, the band gap opening via quantum confinement, which is effective for graphene, becomes ineffective for borophene. Several critical issues with the structural degradation of InSe due to oxygen and humidity at ambient conditions have been studied. The oxidation of monolayer InSe has been explored by examining the roles of light illumination, oxygen, water and defects. Pristine InSe has shown a much lower oxygen affinity than MoS2 and phosphorene. However, the presence of MV and light excitation have significantly accelerated the oxidation by greatly decreasing the barrier through forming chemical oxygen species. These atomic O species, which are associated with strong polar O-In bonds, can quench the defective states of MV, and further act as the adsorption and trapping centres of H2O molecules. The apical O atoms in the form of terminated Se-O bonds have been shown to allow even spontaneous water splitting and the formation of hydroxyl groups at room temperature. Accordingly, the following three strategies have been proposed to suppress the oxidation of InSe: i) insulating InSe from O2 molecules; ii) maintaining the InSe surface stoichiometry; iii) avoiding the exposure of InSe to light illumination. The energetics and charge transfer of small molecules (CO, NO, NO2, H2O, O2, NH3, and H2) adsorbed on antimonene have been considered. NO2 has the strongest adsorption energy among all the considered molecules, which may arise from the coexistence of a large dipole moment of NO2 and resonant molecular levels with the antimonene states. The strong acceptors, like NO2, NO, and O2, bind more strongly to the antimonene surface than the phosphorene surface, while the weak acceptors, like CO, H2, and NH3, show a weaker adsorption. The interaction of O2 with antimonene has been found to be much stronger than that with phosphorene. The found low kinetic barrier for the splitting of the O2 molecule on antimonene suggests that pristine antimonene may undergo oxidation in ambient conditions. Fortunately, the acceptor role of H2O on antimonene, opposite to the donor role in phosphorene, helps to suppress further structural degradation of the oxidized antimonene by preventing the proton transfer between water molecules and oxygen species to form acids. By comparing antimonene with phosphorene and InSe, it has been predicted that the acceptor role of water may be a necessary condition for a good environmental stability of such 2D layers to avoid structural decomposition. Individual 2D materials have been combined to form heterostructures. The investigations of the effect of compressive (tensile) strain on the chemical activity of the in-plane graphene-silicene heterostructure with the H2O molecule have shown that compressive (tensile) strain is able to increase (decrease) the binding energy of the H2O molecule compared with the adsorption on a planar surface. At the same time the charge transfer between H2O molecule and the graphene-silicene sheet can be modulated by strain. The in-plane graphene-silicene heterostructure has been found to be metallic in a strain range from -7% (compression) to +7% (tension). In addition, the modulation of monolayer InSe electronic properties by graphene and BN encapsulation has been found. In particular, graphene (donor) and BN (acceptor) have been found to play an opposite charge donating role in InSe, which is dramatically different from phosphorene, where both graphene and BN play the same role (donor). The changing of the interlayer spacing of the InSe-graphene (BN) heterostructure has been predicted as an effective technique to dramatically change the bands alignment and control the band gap of the heterostructure. This Ph.D. dissertation has explored and explained in detail the unique structural and opto-electronic properties of novel 2D materials and their hybrids. This research will not only help to understand the routes for controlling and modifying the properties of 2D materials and thus to enhance their performance, but also contribute to the development of techniques for the growth, storage and applications of different 2D materials.